The Impact of Work Environment, Motivasion, and Work Discipline on Teacher Performance - Maimunah, Siti; Rozak, Hasan Abdul (Maneggio, 2024)
The purpose of this study is to analyze the influence of the work environment, motivation and work environment on the performance of state elementary school teachers. The data used in this study is primary data obtained from distributing online questionnaires using google forms. Data collection uses a random sampling technique with the Slovin formula so that a sample of 66 teachers was obtained as if the country was the basis as respondents. The analysis tool in this study is by using SPSS software version 26. Specifically, the work environment variable has a significant positive effect on performance, the motivation variable has a significant positive effect on performance, the work discipline variable has a significant positive effect on performance and the work environment variable, motivation and work discipline simultaneously have a positive and significant effect on the performance of state elementary school teachers in Sedan District, Rembang Regency. The determination coefficient test stated that the independent variable had an influence of 48.2% on the performance while the remaining 51.8% was influenced by other variables outside the study